2020
DOI: 10.1002/tox.23091
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Cirrhinus mrigala to second‐generation fluoroquinolone (ciprofloxacin) toxicity: Assessment of antioxidants, tissue morphology, and inorganic ions

Abstract: Ciprofloxacin drugs are a second‐generation fluoroquinolone highly prescribed medication against various bacterial infections in human and aquaculture practices. These drugs are chemically designed to persist in the body long enough to achieve target objectives. Extensive usage has resulted in ciprofloxacin becoming a ubiquitous contaminant in the environment. Unfortunately, the ecotoxicological profiles for ciprofloxacin are scanty. This study was aimed to assess the ecotoxicity of ciprofloxacin at environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 90 publications
(111 reference statements)
0
13
0
1
Order By: Relevance
“…It suggested that the stress and the physiological changes induced by OA persevered. Further, the results of the reduced inorganic ions like calcium and chloride in plasma suggested that dietary OA may cause ionic imbalance as was observed in quinolones‐exposed fish (Ramesh et al, 2021), which, in turn, affects the physiological and osmoregulatory processes of fish. Earlier reports documented that antibiotics tend to bind to ions and reduce their availability in the blood (Guidi et al, 2018) and the gill tissue and chloride cells (Ramesh et al, 2021), thus disturbing normal osmoregulation.…”
Section: Discussionmentioning
confidence: 94%
“…It suggested that the stress and the physiological changes induced by OA persevered. Further, the results of the reduced inorganic ions like calcium and chloride in plasma suggested that dietary OA may cause ionic imbalance as was observed in quinolones‐exposed fish (Ramesh et al, 2021), which, in turn, affects the physiological and osmoregulatory processes of fish. Earlier reports documented that antibiotics tend to bind to ions and reduce their availability in the blood (Guidi et al, 2018) and the gill tissue and chloride cells (Ramesh et al, 2021), thus disturbing normal osmoregulation.…”
Section: Discussionmentioning
confidence: 94%
“…The magnitude of increase crudely re ects the number of affected hepatocytes. Conceptually, the ALP, ALT, and AST are believed to be hepatocellular "leakage" enzymes (Ramesh et al 2021). Although the intensity of vacuolation recouped slightly, it was still observed on day 21 PFD.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in the fish Cirrhinus mrigala exposed to environmentally realistic CIP concentrations (1 μg/L and 1.5 μg/L) there was an increase of the superoxide dismutase activity (SOD) and lipid peroxidation in gills, liver, and kidney, whereas catalase activity (CAT) decreased in gill and liver, but significantly increased in kidney. Moreover, CIP promoted a series of histological anomalies in gills, liver, and kidney tissues (Ramesh et al, 2021). Indeed, antibiotics can also induce malformations affecting the normal development as demonstrated by González-González et al (2021) in zebrafish embryos exposed to AMX.…”
Section: Discussionmentioning
confidence: 99%